Aeetes: A Tragic Figure in the Argonautica of Apollonius Rhodius - Dimitra Karamitsou (Aitia, 2023)
The purpose of this paper is to examine the transition of Aeetes from an epic to a tragic figure in the Argonautica of Apollonius Rhodius. The Argonautica is a generic mixture of both epic and tragic elements. On the one hand, it is an epic poem based on Homeric aesthetics. On the other hand, Apollonius differentiates himself from Homer by promoting different values through his epic. Within the Argonautica, we can distinguish a transition from an epic to a tragic poetic mode. In other words, Apollonius composes an epic that consists of many minor tragedies. Aeetes can be used as an example of this generic transition. He is supposed to be a representative of archaic epic within the Argonautica. However, although Aeetes is represented as an epic figure in the beginning of the poem, he ends up being a tragic figure, in accordance with the definition given by Aristotle in his Poetics.